Strategies for rock slope failure early warning using acoustic emission monitoring. (August 2015) - Codeglia, D; Dixon, N; Fowmes, G J; Marcato, G
Abstract: Research over the last two decades has led to development of a system for soil slopes monitoring based on the concept of measuring Acoustic Emission (AE). A feature of the system is the use of waveguides installed within unstable soil slopes. It has been demonstrated that the AE measured through this technique are proportional to soil displacement rate. Attention has now been focused on the prospect of using the system within rock materials. The different nature of the slope material to be monitored and its setting means that different acoustic trends are measured, and development of new approaches for their interpretation are required. A total of six sensors have been installed in two pilot sites, firstly in Italy, for monitoring of a stratified limestone slope which can threaten a nationally important road, and secondly in Austria, for monitoring of a conglomerate slope that can endanger a section of the local railway. In this paper an outline of the two trial sites is given and AE data collected are compared with other physical measurements (i.e. rainfall and temperature) and traditional geotechnical instrumentation, to give an overview of recurring AE trends. These include clear AE signatures generated by stress changes linked to increased ground water levels and high energy events generated by freeze-thaw of the rock mass.